2022
DOI: 10.31635/ccschem.021.202101584
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization and Multiple-Responsive Recognition of Natural Base Pairs in Water by a Cationic Cage

Abstract: The hydrogen-bonded (H-bonded) base pairs, double H-bonded A•T and triple H-bonded G•C in DNA, are important units for storing, encoding, and expressing genetic information. Owing to the interference from water, however, the formation of H-bonded base pairs from short deoxynucleotide fragments such as mono-or di-deoxynucleotide are not easily achieved in aqueous solutions. Here, we report a host-guest strategy to stabilize H-bonded base pairs of monodeoxynucleotides by a tetraphenylethene (TPE)-based octacatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Recently, we reported that a tetraphenylene-based octacationic cage (1) can recognize biomolecules such as deoxynucleotides, nucleotides, and DNA to exhibit multiple responsive behaviors with fluorescence, circular dichroism (CD), and circularly polarized luminescence (CPL) signals. [34][35][36][37] In theory, 1 with a hydrophobic cavity and water solubility could be used as a molecular container for drug delivery in aqueous solution. [38][39][40] On the one hand, 1 has several advantages in aqueous recognition and detection.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we reported that a tetraphenylene-based octacationic cage (1) can recognize biomolecules such as deoxynucleotides, nucleotides, and DNA to exhibit multiple responsive behaviors with fluorescence, circular dichroism (CD), and circularly polarized luminescence (CPL) signals. [34][35][36][37] In theory, 1 with a hydrophobic cavity and water solubility could be used as a molecular container for drug delivery in aqueous solution. [38][39][40] On the one hand, 1 has several advantages in aqueous recognition and detection.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, a TPE-based octacationic cage with four pillars, which has a closed cavity (Scheme 1a, left), has been constructed for host–guest recognition, fluorescent sensors, energy and electron transfer, and drug delivery. 18 Here, we report a TPE-based hexacationic molecular cage ( 1 ) with only three pillars, which has an open cavity (Scheme 1a, right). Compared with the four-pillared cage, 1 with an open cavity exhibits 1 : 2 or 1 : 1 host–guest recognition for large nicotinamide adenine dinucleotide (NAD) molecules including NADH and NAD + with dual responses of circular dichroism (CD) and fluorescence in water.…”
mentioning
confidence: 92%
“…9–13 Given their good fluorescence and novel structure, TPEs have been successfully introduced into the supramolecular and material fields for the construction of macrocyclic compounds, 8 metal–organic frameworks (MOFs) and covalent-organic frameworks (COFs). 14,15 In previous reports, our group has developed a series of TPE-based monocyclophanes, 16 dicyclophanes, 17 3D cages, 18 and supramolecular organic frameworks (SOFs) 19 for molecular recognition and luminescence materials. Particularly, a TPE-based octacationic cage with four pillars, which has a closed cavity (Scheme 1a, left), has been constructed for host–guest recognition, fluorescent sensors, energy and electron transfer, and drug delivery.…”
mentioning
confidence: 99%
“…Chirality is vital to biological processes and widely exists in various biological structures at the molecular level, including polysaccharides, proteins and DNA. 10 Incorporation of chirality into artificial functional materials provides new objectives towards chiral separation, 11 stereospecific catalysis, 12 chiral recognition, 13 and unique chiroptical properties. 14 Self-assembly depending on chiral recognition and discrimination has been used to prepare chiral functional supramolecular materials through noncovalent interactions such as electrostatic interactions, 15 π–π interactions, 16 hydrogen bonding, 17 and metal-coordination bonds.…”
Section: Introductionmentioning
confidence: 99%